THE INFLUENCE OF TRADE WARS, INFLATION, POLITICAL UNCERTAINTY, AND INTEREST RATE DECISIONS ON BITCOIN PRICES - Andini Prisilia Simorangkir; Sannia Noviantri; Steffania Tanoto; Afriza Amir (ZILLZELL MEDIA PRIMA, 2026)
This research examines to test the impact of interest rate decisions, political instability, inflation, and trade disputes on the price of Bitcoin from 2020 to 2025 is the purpose of this research. Descriptive and confirmative approaches, which are quantitative, are used in this study. The secondary time series data used in this study is sourced from various global sources, including government databases and publications. This analytical method uses multiple linear regression with classical assumption testing. This includes normality testing, multicollinearity, heteroskedasticity, and autocorrelation. Furthermore, the hypothesis is tested using the F test to identify the simultaneous effect and the t test to identify the partial effect. The model's ability to explain bound variables is then measured through the determination coefficient, known as Adjusted R². The analysis found that factors such as inflation, political instability, trade conflicts, and interest rate decisions all contribute to the price of Bitcoin. Each of these factors has a unique and partial effect on the rise and fall of the price of Bitcoin. This research provides an overview that global macroeconomic factors have an important role in determining the price dynamics of crypto assets, especially Bitcoin.